ACTH vs Vigabatrin in Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The comparative efficacy and safety of ACTH (110 IU/m2 once daily for 15 days) and vigabatrin (100-150 mg/kg/daily in bid doses) was evaluated by a retrospective analysis of medical records of 42 infants (21 in each group) with infantile spasms and hypsarrhythmia treated at the Universite de Montreal, Hopital Sainte-Justine, Montreal, Canada.